Enabling rapid and cost-effective creation of massive pervasive games in very unstable environments - Wietrzyk, Bartosz; Radenkovic, Milena (2007)
Pervasive gaming is a new form of multimedia entertainment that extends the traditional computer gaming experience out into the real world. Through a combination of personal devices, positioning systems and other sensors, combined with wireless networking, a pervasive game can respond to player's movements and context and enable them to communicate with a game engine and other players. We review our recent deployment examples of pervasive games in order to explain their distinctive characteristics as wireless ad-hoc networking applications. We then identify the network support challenges of scaling pervasive games to include potentially mass numbers of players across extremely heterogeneous and unreliable networks. We propose a P2P overlay capable of storing large amount of game related data, which is the key to combating the loss of coverage and potential dishonesty of players. The proposed protocol decreases the deployment costs of the gaming infrastructure by self organization and utilizing storage space of users' devices. We demonstrate scalability and increased availability of data offered by the proposed protocol in simulation based evaluation